2017
DOI: 10.1177/1479164117712176
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of the left atrial appendage in patients with diabetes mellitus

Abstract: Despite patients with diabetes mellitus are high-risk patients, the outcome of percutaneous left atrial appendage closure is similar to patients without diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…So far, procedural safety of LAAC with Amplatzer occluders was assessed according to single factors of the CHADS 2 or HAS‐BLED score and similar results were found for patients at higher age, 19 with reduced kidney function, 20 or diabetes mellitus 21 and two studies have reported safety data in patients with very high stroke risk. Kebernik et al published major procedural complication rates of 7.3% in 96 patients with a median CHADS 2 score of 4 points in patients receiving Amplatzer‐LAAC 22 .…”
Section: Discussionmentioning
confidence: 70%
“…So far, procedural safety of LAAC with Amplatzer occluders was assessed according to single factors of the CHADS 2 or HAS‐BLED score and similar results were found for patients at higher age, 19 with reduced kidney function, 20 or diabetes mellitus 21 and two studies have reported safety data in patients with very high stroke risk. Kebernik et al published major procedural complication rates of 7.3% in 96 patients with a median CHADS 2 score of 4 points in patients receiving Amplatzer‐LAAC 22 .…”
Section: Discussionmentioning
confidence: 70%
“…The post-implant drug regimen was discontinuation of OAC followed by dual-antiplatelet therapy with aspirin 100 mg and clopidogrel 75 mg daily for 3 to 6 months, following a loading dose of clopidogrel of 600 mg [ 15 ]. All patients were followed up with TOE after 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…However, major bleeding risk of OACs remain high and higher costs of OACs lead to poorer cost effectiveness [12]. Recently, LAA closure (LAAC) has been shown not to be inferior to OAC for stroke prevention, according to the PROTECT-AF and PREVAIL clinical trials [13][14][15]. Left atrial appendage closure thus plays an important role as an alternative to OAC for stroke prevention in patients with AF, reducing the bleeding risk [16][17][18], and could be a potential alternative to OAC in patients with AF and CDK.…”
Section: Introductionmentioning
confidence: 99%
“…Although AF patients with DM are at higher risk for bleeding and thromboembolism, outcomes after LAAC appear comparable to those in non-diabetics. 104,105 However, a recent multicenter study of 277 patients with LAAC and prior gastrointestinal bleeding reported DM as a risk factor for higher mortality after LAAC. 106 Smoking was identified as an independent predictor of device-associated thrombus after LAAC with one device.…”
Section: Left Atrial Appendage Closure (Laac)mentioning
confidence: 99%